Good and bad institutions: Is the debate over? ; cross-country firm-level evidence from the textile industry - Sumon K. Bhaumik; Ralitza Dimova (Institute for the Study of Labor (IZA), 2011)
Using firm-level data from nine developing countries we demonstrate that (a) certain institutions like restrictive labour market regulations that are considered to be bad for economic growth might be beneficial for production efficiency, whereas (b) good business environment which is considered to be beneficial for economic growth might have an adverse impact on production efficiency. We argue that our results suggest that the debate about the implications of institutional quality is far from being over, and classification of institutions into good and bad might be premature.
urn:nbn:de:101:1-201104113446
Keywords: D02; D23; D24; 330; institutional quality; production efficiency; stochastic frontier model; Institutionelle Infrastruktur; Institutionalismus; Produktivität; Wirtschaftliche Effizienz; Textilindustrie; Technische Effizienz; Industriestaaten